Social evolution in toothed whales - Connor, RC; Mann, J; Tyack, PL; Whitehead, H (1998)
Two contrasting results emerge from comparisons of the social systems of several odontocetes with terrestrial mammals. Researchers have identified remarkable convergence in prominent features of the social systems of odontocetes such as the sperm whale and bottlenose dolphin with a few well-known terrestrial mammals such as the elephant and chimpanzee. In contrast, studies on killer whales and Baird's beaked whale reveal novel social solutions to aquatic living. The combination of convergent and novel features in odontocete social systems promise a more general understanding of the ecological determinants of social systems in both terrestrial and aquatic habitats, as well as the relationship between relative size and social evolution.